Identificación de los factores de riesgos ergonómicos y salud ocupacional de los funcionarios del Registro Civil de la Agencia Latacunga. Diseño de un sistema de control. - Segovia Armas, Ernesto Xavier (2015)
In this research work was done a study of the ergonomic risk factors in the Civil Registry at Latacunga Agency to design a control system. the identification of more significance ergonomic risk factors was done using the matrix of the National Institute of safety and hygiene of the work recommended by the Ministry of labour relations, then for the evaluation of jobs the method RULA and RULA OFFICE were applied to determine the exposure of all detected ergonomic risk factors as critical in the muscular skeletal disorders to a population and sample of 59 public servants. The design of a system of control that is the product of this work determined the control measures as high risk such as: content of work, conditions of space, comfort of work and organizational factors using formats and structure recommended by the Ecuadorian legislation and international standards through its dissemination and application creating a culture of prevention of occupational risks , through actions that reduce the effects of health that are exposed in the performance of their professional activities.